Applying bicoherence analysis to spacecraft observations of Langmuir waves. Issue 5 (5th March 2014) - Graham, D. B.; Malaspina, D. M.; Cairns, Iver H.
<x xml:space="preserve">Abstract</x> In type II and type III solar radio bursts and planetary foreshocks, the processes which convert Langmuir waves (LWs) to transverse waves are not well understood. One of the proposed mechanisms for generating transverse waves involves electrostatic (ES) decay followed by coalescence of two LWs. One of the tests used to identify this process is bicoherence analysis. Bicoherence has been applied to spacecraft observations of LWs to yield results consistent with ES decay and coalescence. However, recent work has shown that the harmonic fields produced by LWs are more consistent with sheath rectification and nonlinear currents. It is shown here that sheath rectification and nonlinear currents yield bicoherences similar to those expected for ES decay and coalescence, explaining the bicoherences associated with spacecraft observations of LWs. These results show that bicoherence alone cannot be used to identify ES decay and coalescence and emphasize the importance of sheath rectification.